Análise comparativa da eficiência das compras de hortifrútis da Universidade Federal da Paraíba - Nóbrega, Marcelo Moura (2017)
The importance of public purchases for the running of the state machine, and econo mic and social development is unquestionable. However, the governmental acquisitio ns appear as one of the major problems of Public Management despite the announce ment of the achievement of billionaire economies by electronic bidding. As this expense containment is calculated based on the difference between the reference price and purchase price, in many cases, it does not lead to efficient acquisitions. In an attempt to promote a higher efficiency of public purchases, the Federal Government has been implementing a series of changes, based on a new type of public efficiency, which considers, besides the economic dimension, the social and environmental ones, too. Among the latest changes, we have - besides the introduction of new rules for favoring biddings focused on the small rural producer - the strengthening of the performance assessment use as a tool for management quality. However, in spite of the fact that is mandatory to respect the laws related to public purchases, which should be sustainable, and performance assessment, which should be done by everyone, such measures have not been followed and only seldom occur. Thus, for the changes referring to the food purchases for the federal public offices are not included in the list of sustainability related policies that are not followed, and for family agriculture not to be a victim of lack of support, the present study investigated the efficiency of purchases of fruits and vegetables in UFPB, as from a comparison of those with performance parameters achieved by other federal offices based in Paraíba. This is a descriptive and analytic, quantitative and qualitative, documental research done by means of a case study. Outcomes show that purchases of fruits and vegetables by the referred institution appear as the most efficient, regarding both a general view, and an economic and social dimension, as well. Nevertheless, UFPB is still far from reaching the ideal performance, that is, with maximum efficiency. Thus, it shall be concluded that UFPB is in need of reconsidering the aspects of its management in relation to food purchases so that its more advantageous proposal choices should be made in accordance with what society expects and what is determined by the law.